Pollination of wild lady slipper orchids Cypripedium yunnanense and C. flavum (Orchidaceae) in south-west China: Why are there no hybrids? - Hans Bänziger (2018)
Rewardless kettle-trap flowers Cypripedium yunnanense and C. flavum were watched for pollinators during 73 and 101 man-hours, respectively, in north-west Yunnan at 3490-3590 m a.s.l. They differ from typical Cypripedium, such as C. calceolus, in having a broad infolded flap of the lip extending all around the entrance of the pouch (instead of being restricted to the vicinity of the staminode) and in the flap not being slippery. Cypripedium yunnanense is pollinated by Lasioglossum zonulum euronotum (Halictidae), and C. flavum is pollinated by Andrena orchidea and Andrena sp. (Andrenidae, two of nine new hymenopterans discovered at the sites). The bees do not inadvertently fall into the trap by slipping (as often occurs in other slipper orchids), but enter it by crawling down the flap in full control of their movements. No natural hybrids between the two orchids are known, although they occur in close-by or mixed stands, are co-flowering and size compatible with regard to their pollinators, and produce fruits following manual cross-pollination in situ. Analyses of the (non-Cypripedium) pollen carried indicate that: (1) the two andrenids are probably oligolectic; (2) the andrenids and the halictid do not share the same flower species; and (3) the halictid is polylectic. Points (1) and (2) are probable reasons for the lack of hybrids. The other reason why Lasioglossum zonulum euronotum does not visit C. flavum despite being polylectic may be the flower's odour; cases of discrimination of closely related flowers by polylectic Lasioglossum have been reported elsewhere. Blow flies Calliphora vomitoria and Calliphora pattoni (Calliphoridae) also enter the orchids, some smearing themselves with pollen, yet they are not pollinators. They are too large to leave by the exit and die imprisoned. However, they may be accidental pollinators of the rather larger C. tibeticum present at the sites. Such accidental pollinators probably play an important role in the evolution of new pollination syndromes. © 2008 The Linnean Society of London.